High CD4+/CD8+ Intratumour Ratio is associated with favourable outcome in triple-negative Breast Cancer - Thian, Q.Z.; Reena Rahayu Md Zin; Thong, Q.X.; Muaatamarulain Mustangin; Nurwahyuna Rosli; Afzan Adam (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Triple-negative breast cancer (TNBC) is a heterogenous breast cancer subtype which accounts for 10-15% among all diagnosed breast cancers. There is increased resistance of TNBC to conventional chemotherapy and hormonal therapy due to lack of oestrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) expression. Mutual relationship and interactions between both CD4+ and CD8+ T lymphocytes are very crucial for eliciting adaptive immune system during anti-cancer immune response. This study aimed to determine the ratio of CD4+ and CD8+ T lymphocytes in TNBC by immunohistochemistry assay and to investigate the association of CD4+ and CD8+ tumor-infiltrating lymphocytes (TILs) with survival outcome. Quantification of both immunostaining TILs subset was done using conventional light microscope. A wide range of CD4+ and CD8+ TILs subset was found within intratumor stroma of TNBC with population mean score of 0.93 and 0.53, respectively. However, the difference of mean population between both TILs subsets was insignificant overall (P-value of CD4+= 0.484; CD8+= 0.835) when compared statistically using independent t-test. The ratio of CD4+/CD8+ in intratumor stroma ranged from 0.50-5.88 among all TNBC subtypes. The high CD4+/CD8+ ratio within intratumor stroma showed favorable association with survival outcome during the 2 years’ follow-up.